2005
DOI: 10.4049/jimmunol.175.9.5839
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulation of CD4+ T Cells from Lupus Patients by a Promiscuous, Protective Peptide Analog

Abstract: A peptide encompassing residues 131–151 of the spliceosomal U1-70K protein and its analog phosphorylated at Ser140 were synthesized as potential candidates for the treatment of patients with lupus. Studies in the MRL/lpr and (NZB × NZW)F1 lupus models have demonstrated that these sequences contain a CD4+ T cell epitope but administration of the phosphorylated peptide only ameliorates the clinical manifestations of treated MRL/lpr mice. Binding assays with soluble HLA class II molecules and molecular modeling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 41 publications
1
36
0
1
Order By: Relevance
“…16,17,20,21 In addition, we have previously reported the importance of the phosphorylated Ser140 residue in modulating the autoimmune response. 18,19 Therefore, we propose that the Materials and Methods Antibodies. Antibodies against peptides encompassing residues 131-151, the residues 131-151 with a phosphorylated Ser140 and 183-202 (containing no serine residues) of the U1-70K protein were raised in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,20,21 In addition, we have previously reported the importance of the phosphorylated Ser140 residue in modulating the autoimmune response. 18,19 Therefore, we propose that the Materials and Methods Antibodies. Antibodies against peptides encompassing residues 131-151, the residues 131-151 with a phosphorylated Ser140 and 183-202 (containing no serine residues) of the U1-70K protein were raised in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We previously found that a peptide encompassing residues 131-151 in the RRM of the U1-70K protein and phosphorylated at Ser140 (peptide P140) was recognized by CD4 þ T cells from mice and patients with lupus and protected young lupus mice against the disease in contrast to the nonphosphorylated peptide, which was not tolerogenic. 18,19 In addition, for unknown reasons, the apoptotic form of the protein is a preferred target of autoantibodies. 20,21 Consequently, we tried to clarify the pathway leading to an immunogenic protein by evaluating the changes in the phosphorylation status of the U1-70K protein during apoptotic conditions with a particular focus on Ser140.…”
mentioning
confidence: 99%
“…A T-cell epitope located in the RNP1 motif present within the RRM of the U1-70K protein has been characterized using T cells from patients with lupus and MRL-lpr and (NZB Â NZW)F1 mice [168,186,187]. T cells from MCTD patients recognize five distinct epitopes on U1-70K that are also located within the RNA-binding domain [188].…”
Section: Autoreactive T Cellsmentioning
confidence: 99%
“…These unaltered, native peptide epitopes halt progression of lupus nephritis upon tolerization in high-dose soluble form and importantly for human therapy, the peptides are also effective in delaying/preventing lupus nephritis in subnanomolar doses (ϳ0.37 nM or 1 g), administered s.c. to lupus-prone SNF 1 mice (2,3,15). This dose is 300-to 1000-fold less than peptides from other nucleoproteins or unrelated peptides from Ig V regions (CDR) that are being tried as therapeutic agents (4,5,16,17).…”
Section: Low-dose Peptide Tolerance Therapy Of Lupus Generates Plasmamentioning
confidence: 99%